Kolaviron Improved Resistance to Oxidative Stress and Inflammation in the Blood (Erythrocyte, Serum, and Plasma) of Streptozotocin-Induced Diabetic Rats - Omolola R. Ayepola; Nicole L. Brooks; Oluwafemi O. Oguntibeju (The Scientific World Journal)
Aims. Bitter kola seed (Garcinia kola, family: Guttiferae) has been used as a social masticatory agent in Africa for several years and is believed to possess many useful medicinal properties. The present study evaluates the antioxidative, anti-inflammatory, and antilipidemic effects of kolaviron (an extract from the Garcinia kola seeds) in the blood of streptozotocin- (STZ) induced diabetic rats. Methods. Diabetic rats were treated with kolaviron (100 mg/kg b·wt) orally, five times a week for a period of six weeks. Serum glucose and HBA1C concentrations were estimated in experimental groups. The activities of antioxidant enzymes: catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPX) (in erythrocytes) as well as plasma concentration of malondialdehyde (MDA), a product of lipid peroxidation, oxygen radical absorbing capacity (ORAC) and ferric-reducing antioxidant power (FRAP) were investigated. Serum levels of proinflammatory cytokines and growth factor: interleukin- (IL-) 1, monocyte chemotactic protein-1 (MCP-1), and vascular endothelial growth factor (VEGF), respectively, were also analyzed. Results. Kolaviron treatment markedly improved antioxidant status and abated inflammatory response evidenced by reduction in the levels of proinflammatory cytokines and growth factor, lipid peroxidation product, and the restoration of activities of erythrocyte antioxidant enzymes in the blood of diabetic rats. Conclusion. Kolaviron improved antioxidant status, reduced inflammation, and protected against hyperglycemic-induced oxidative damage in the blood of diabetic rats.